Diagnostic Value of Barium Esophagogram and Bernstein Test in Patients with Esophagitis - Juwanto Juwanto; Chudahman Manan; Abdul Aziz Rani (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2001)
From the 19th of July to the 19th of October 1999, we conducted a study to evaluate the diagnostic capabilities/benefits of the double contrast barium esophagogram in patients with esophagitis. The sample patients were taken from patients with reflux-type dyspepsia who visited the out patient clinic of the Sub-department of Gastroenterology of the Department of Internal Medicine of the Faculty of Medicine of the University of Indonesia/Cipto Mangunkusumo Hospital, Jakarta. During the duration of study, 32 patients fulfilled the criteria for inclusion, and did not fulfill the criteria for exclusion. All of the subjects underwent double contrast barium esophagogram, Bernstein test, and endoscopy of the upper gastrointestinal tract, as well as biopsy of the lower third esophageal mucosa. The chief complaints for reflux type dyspepsia were found in the following order: pyrosis/heartburn (56.26%), acid/sour taste in the mouth (12.5%), chest pain (9.38%), swallowing disturbance (6.25%), breathing difficulties (6.25%), belching (6.25%), and palpitation (3.12%). From  the  32  patients  with  reflux  type  dyspepsia  that  underwent  double  contrast  barium esophagogram, 10 patients (31.25%) were found positive for esophagitis, and the remaining 22 patients were found to be negative (68.75%). Bernstein test found 11 patients (34.37%) positive and 21 (65.63%) negative, while endoscopy of the upper gastrointestinal tract showed positive esophagitis in 25 patients (78.13%) and negative in 7 patients (21.87%). The degree of accordance between double contrast barium esophagogram and the Bernstein test or even a combination of the two was unsatisfactory in diagnosing esophagitis in reflux type dyspepsia. Based on this, this study concludes that double contrast barium esophagogram and Bernstein are incapable of replacing endoscopic examination in establishing the diagnosis of esophagitis.    Keywords: esophagitis, esophagogram, Bernstein test